Ambient N2-to-NH3 fixation over a CeO2 nanoparticle decorated three-dimensional carbon skeleton. Issue 14 (27th June 2022) - Liu, Chengchen; Li, Shaoxiong; Li, Zerong; Zhang, Longcheng; Chen, Haijun; Zhao, Donglin; Sun, Shengjun; Luo, Yonglan; Alshehri, Abdulmohsen Ali; Hamdy, Mohamed S.; Liu, Qian; Sun, Xuping
Abstract : A CeO2 nanoparticle decorated three-dimensional carbon skeleton derived from Juncus performs for electrocatalytic N2 -to-NH3 conversion, capable of attaining a large NH3 yield of 33.4 μg h −1 mgcat. −1 and a faradaic efficiency of 6.1% at −0.6 V vs. RHE. Abstract : Electrochemical N2 reduction emerges as a promising substitute to the Haber–Bosch process for ambient NH3 synthesis, but it is a tough task to develop efficient catalysts. Here, we propose a CeO2 nanoparticle decorated three-dimensional carbon skeleton derived from Juncus as an active and stable electrocatalyst for N2 -to-NH3 conversion. In N2 -saturated 0.1 M Na2 SO4, this nanohybrid attains a large NH3 yield of 33.4 μg h −1 mgcat. −1 with a faradaic efficiency of 6.1% at −0.6 V vs. the reversible hydrogen electrode. Furthermore, it also possesses favorable durability.